Exploring Digital Ta‘aruf through the Lens of Maqashid al-Shariah: A Case Study of Hifz al-Din at Biro Jodoh Rumaysho - Athifah, Zulfa; Mulyani, Maulidia; Kamiliyah, Zahrotul ‘Ilmiya; Agustin, Balqis Ratu (Universitas Islam Indonesia, 2025)
The digitalization of social interactions has transformed various aspects of life, including the practice of finding a partner. One emerging phenomenon is the practice of digital ta’aruf, a process of introducing matchmaking between men and women conducted through digital platforms and online. This study aims to provide an empirical analysis of how hifz al-din is implemented in the digital ta’aruf system. Using a qualitative case study approach, the study specifically discusses the gaps in digital ta’aruf practices from the perspective of Hifz Al-din at the Rumaysho Matchmaking Bureau (BJR), a digital matchmaking agency based in Gunung Kidul, Yogyakarta. Data were collected through two months of in-depth interviews with matchmaking agency managers and other personnel. The results show that, first, the digital ta’aruf process at BJR is carried out in a structured manner in several stages supported by religious education, supervised interactions, and ethical communication guidelines. Not only does this mechanism serve as a matchmaking facilitator, it also serves to maintain religious values ​​by guiding pre-marital interactions within the boundaries of Islamic law. Second, from the perspective of maqashid al-shari’ah, hifz al-din in this context is not limited to protecting faith, but also includes preserving moral behavior and social interaction patterns to prevent practices that lead to moral decay. Finally, the findings show that digital technology, when properly regulated, can serve as a means of protecting religion and not a threat, and can provide a reference for the development of a maqashid-based digital ta’aruf platform.